TINJAUAN YURIDIS TENTANG PERATURAN PERIZINAN USAHA PERIKANAN - Indrastuti, Lusia - (Universitas Slamet Riyadi, 2012)
Abstract:Licensing regulations on fishing effort is regulatory role in maintaining thesustainability of fish resources and the environment, and improve the welfare offishermen's economic contribution to the state in accordance with the objectives offisheries development.According to Law No. 31 of 2004 on Fisheries is distinguishedfisheries business license on fishing and fish breeding. Regulation of the Minister ofMarine Affairs and Fisheries No. 12 / MEN/2012 on Business fisheries on the high seasis concerned with conservation of fish resources, fishing license can be used as a toolto control fishing effort to pay attention to the fish resource conservation issues.Keywords: control, conservation, fish resources.